Knowledge of the population of the northern state of Espírito Santo and Northeast of the state of Minas Gerais on Herpes Viruses and Perspectives of Care of Dentistry - Souza, Julianna Godoi de; Silva, Wanessa Soares Luiz; Nunes, Marcus Antonius Da Costa; Guisso, Luana Frigulha; Abreu, Juscélio Clemente de; Rezende, Bruno Augusto de; Freitas, Kenia Roberta Reuter de; Amorim, Patrícia Brandão; Ricardo, Eci Fernandes; Gomes, Eugênio Maria; Silva, Daniel Rodrigues (International Journal for Innovation Education and Research, 2019)
This study aimed to measure the level of knowledge of HZV in northern municipalities in the state of Espirito Santo and Northeast of Minas Gerais in order to analyze and compare the variables investigated on the herpes virus. Specifically aims to understand the perception of this population about the forms of contagion, activating factors of the virus and the mechanism of access to information. Therefore, we carried out a literature review and research linked to it through the study method of approach to the case. In selected areas, individuals from 10 cities in the North of the Holy Spirit and Northeast of Minas Gerais, participated answering structured questionnaire. The results showed that a significant percentage have little information or complete ignorance about the disease, modes of transmission and its consequences for health. Much of the sample is unaware of the importance of the dentist to provide information and to treat cold sores, in addition to a lack of health services have been observed to provide information about the disease, its clinical signs and prevention, through educational activities for the population and 19% of the population has herpes labialis. Thus, it is concluded that most educational measures should be carried out, understanding that the greater the knowledge, the lower the infection rates, leading individuals to prevent and to treat when detected the expression of pathogenic signals. in addition to a lack of health services have been observed to provide information about the disease, its clinical signs and prevention, through educational activities for the population and 19% of the population has herpes labialis. Thus, it is concluded that most educational measures should be carried out, understanding that the greater the knowledge, the lower the infection rates, leading individuals to prevent and to treat when detected the expression of pathogenic signals. in addition to a lack of health services have been observed to provide information about the disease, its clinical signs and prevention, through educational activities for the population and 19% of the population has herpes labialis. Thus, it is concluded that most educational measures should be carried out, understanding that the greater the knowledge, the lower the infection rates, leading individuals to prevent and to treat when detected the expression of pathogenic signals.